Clinical Evaluation of a Monoclonal Antibody-based Enzyme Immunoassay for Fibrin Degradation Products in Patients with Clinically Suspected Pulmonary Embolism - Gillavry, Melvin R. Mac; de Monyé, Wouter; Lijmer, Jeroen G.; Nieuwenhuizen, Willem; Büller, Harry R.; Huisman, Menno V.; Brandjes, Dees P. M.; the ANTELOPE-Study Group; on behalf of (Thrombosis and Haemostasis, 2000)
We prospectively evaluated the diagnostic accuracy of the Fibrinostika® FbDP assay in 304 consecutive patients with suspected pulmonary embolism and examined potentially useful cut-off points at which the disease can be excluded. The prevalence of pulmonary embolism was 31%. The assay generated an area under the Receiver Operating Characteristic curve of 0.79 (95% CI 0.73–0.84). A cut-off point of 0.05 µ,g/ml yielded a sensitivity, specificity, negative predictive value and an exclusion efficiency of 100% (95% CI 96–100), 5% (95% CI 2–9), 100% (95% CI 69–100) and 3% (95% CI 2–6), respectively. A clinically useful cut-off point seems to be 0.11 µ,g/ml which corresponded with a sensitivity, specificity, negative predictive value and an exclusion efficiency of 96% (95% CI 90–99), 27% (95% CI 24–28), 93% (95% CI 84–98) and 20% (95% CI 16–25), respectively. We conclude that the assay has potential clinical utility for the exclusion of pulmonary embolism, but it cannot be used as a sole test.
Keywords: Fibrin degradation products; pulmonary embolism; diagnosis